2020
DOI: 10.1108/jima-08-2019-0175
|View full text |Cite
|
Sign up to set email alerts
|

Role of halal literacy and religiosity in buying intention of halal branded food products in India

Abstract: Purpose This study aims to investigate the influence of religiosity (intrinsic and extrinsic) and halal literacy on the intention of Muslim consumers to purchase halal branded food products in India. An extended version of the theory of planned behaviour (TPB) was used as a framework. Apart from religiosity and halal literacy, the influence of attitude, social norms and perceived behavioural control of halal on buying intention were also tested. Design/methodology/approach The study uses a survey design. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
47
0
7

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(78 citation statements)
references
References 105 publications
(137 reference statements)
4
47
0
7
Order By: Relevance
“…This study still debates research gap inconsistencies of previous studies on purchasing behavior in halal products. It is like research (Khan et al, 2022), which found that religious belief was not an essential factor in influencing the purchase intention of halal cosmetics. However, another study uncovered that the religiosity level was statistically significant in influencing attitudes toward halal products (Ahmadova & Aliyev, 2020).…”
Section: Introductionmentioning
confidence: 74%
See 1 more Smart Citation
“…This study still debates research gap inconsistencies of previous studies on purchasing behavior in halal products. It is like research (Khan et al, 2022), which found that religious belief was not an essential factor in influencing the purchase intention of halal cosmetics. However, another study uncovered that the religiosity level was statistically significant in influencing attitudes toward halal products (Ahmadova & Aliyev, 2020).…”
Section: Introductionmentioning
confidence: 74%
“…The halal label/logo aids Muslim consumers in making food selection decisions (El-Bassiouny, 2014). Previous studies have proven that religiosity affected consumer purchase intentions (F. Amalia, 2020;Haque et al, 2018;Iranmanesh et al, 2019;Khan et al, 2022;Zakaria et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…However, it differs from the study carried out by Ningtyas et al (2021) and Ikhsan and Sukardi, (2020) suggesting that although attitude and behavioral control had a positive and significant influence on purchase interest in halal-certified products, subjective norms had no positive and significant influence on buying interest in halal-certified products. Khan et al (2022) follow up reasons for the insignificancy that neither intrinsic nor extrinsic religiosity had a direct influence on purchase intention. A previous study also describes that Halal labels and knowledge do not have a significant influence on consumer's desire to buy halal products in Japan (Ratih et al, 2021).…”
Section: ~102~mentioning
confidence: 91%
“…Proposisi yang dapat diangkat dalam variabel ini adalah penekanan pada informasi mengenai label halal (A. Khan, Arafat, & Azam, 2020;Shah, Azhar, & Bhutto, 2019), penekanan pada produk yang dapat memberikan manfaat (Awan, Siddiquei, & Haider, 2015;Jamal & Sharifuddin, 2015;Yeo, Mohamed, & Muda, 2016).…”
Section: Tinjauan Pustaka Dan Perumusan Hipotesisunclassified